Análise normativa de ensaio de prova de carga estática e estudo de caso em ponte de concreto armado - CAMARGO, Luis Faruk Entringer de (2022)
Recently, there was a change in the road network in Pará, characterized by the replacement of wooden bridges with concrete bridges. In this context, load tests are defined as a set of activities designed to analyze the performance of a structure. Thus, this work presents a comparison between Brazilian (ABNT NBR 9607, 2019), Spanish (Ministerio de Fomento, 2009), American (ACI 318, 2019), German (DAfStb, 2000) and Czech (CSN 73 6209, 1996) standards of static load test, as well as the evaluation of the static load test carried out on the bridge over the Jacaré River. The comparison between normative recommendations was carried out taking into account: motivations for carrying out a load test; pre-load test activities; monitoring points; intensity and loading steps; stop and acceptance criteria. This comparison shows that regarding the activities carried out before the load test, the Brazilian standard presents more detailed topics than other recommendations, also having the greatest amount of motivations for carrying out a load test. However, although they are more detailed, they do not require the application of load proof in any of their motivations, thus minimizing the use of this tool. The criteria adopted for the evaluation of the load test carried out on the bridge over the Jacaré River were: opening of cracks; deformations in the spar reinforcement and concrete surface, deformations in the stirrup; and maximum and residual vertical displacements. Regarding the parameter for crack width, the Brazilian recommendations were consistent with the other standards, differing only from the German standard, which is due to the latter being established as a function of maximum cracks and variation of residual crack width. For maximum displacements, the Brazilian and American regulations adhere to design limits, thus, differing from the Spanish and Czech recommendations that present intervals as a function of the theoretical prediction. Due to residual displacements, the Brazilian standard has the lowest permitted residual displacement (5%), being the most rigorous in this criterion compared to the other standards (average of 16%). The results obtained demonstrate the acceptance of the bridge over the Jacaré River due to: opening of cracks, for all normative recommendations; deformation in the stringer and compressed face of the concrete, only for the German standard; maximum displacement, only for the Brazilian standard (with limits 25 times higher than the average of the other standards); and residual displacements, for all recommendations.